VirusTAP: Viral Genome-Targeted Assembly Pipeline - Yamashita, Akifumi; Sekizuka, Tsuyoshi; Kuroda, Makoto (Frontiers in Microbiology, 2016)
Although next-generation sequencing (NGS) technology provides a comprehensive means with which to identify potential pathogens from clinical specimens, simple and user-friendly bioinformatics pipelines are expected to obtain the entire viral genome sequence, subsequently providing traceability, based on extensive molecular phylogenetic analyses. We have developed a web-based integrated NGS analysis tool for the viral genome (virus genome-targeted assembly pipeline: VirusTAP), which includes extensive sequence subtraction of host- or bacteria-related NGS reads prior to de novo assembly, leading to the prompt and accurate assembly of viral genome sequences from metagenomic NGS reads. The VirusTAP web site is at https://gph.niid.go.jp/cgi-bin/virustap/index.cgi/.